PUBLIC PROCUREMENT: HOW CAN LEGISLATIVE REFORMS AND TECHNOLOGICAL INNOVATIONS BE HARNESSED TO EFFECTIVELY COMBAT CORRUPTION IN UZBEKISTAN? - Mardieva, Laylo (Educational Research in Universal Sciences, 2023)
Corruption has found a fertile root in public procurement, a pillar of contemporary government, calling for a renewed commitment to strengthening the legal and institutional ramparts that protect the ideals of transparency and integrity. This article offers a conceptual examination of the corruption issue in the public procurement sector of the Republic of Uzbekistan, as well as proposals for statutory changes and technical developments to address it. This work delves into the intricate dynamics of corrupt practices by putting together existing literature, legislation, and empirical data. It explains the key legal factors that create opportunities for corruption in public procurement. The author examines the system of preventing and combating corruption in public procurement from a critical standpoint, drawing attention to its constituent parts while assessing its overall degree of development and efficacy in light of available academic and regulatory-legal literature. In addition, this article conducts a comparative analysis of legislative frameworks and reforms, investigating various jurisdictions’ experiences in implementing stringent regulations and technological innovations to combat corruption. This article contributes to the continuing conversation on corruption in public procurement by outlining a path for developing legislative frameworks and using the power of technology to create a more equal, just, and prosperous future.